Cultural Representation in Chinese Texts in the Book 來！學華語 (Let’s Learn Mandarin) - Hijrah Rahma Surya; Asfa Sima; Arabia Amran (Interference: Journal of Language, Literature, and Linguistics, 2025)
Abstrak. This study aims to analyze cultural representations in Mandarin dialogue texts in the book 來！學華語 (Let’s Learn Mandarin). This study uses a qualitative approach with a descriptive-analytical method and a Critical Discourse Analysis approach modeled after Norman Fairclough. The research data are dialogue texts containing cultural elements, such as greeting systems, polite expressions, family values, and social interaction patterns of Chinese/Taiwanese society. The results show that the dialogue texts in the book represent culture predominantly through the values of politeness, social hierarchy, collectivism, and social harmony. This is evident from the use of kinship greeting systems, polite expressions, and communication patterns that avoid direct conflict. In addition, it was found that power relations are also represented through differences in language use based on social status Keywords: Cultural Representation, Critical Discourse Analysis, Mandarin, Textbooks, Dialogue Texts